2022
DOI: 10.48550/arxiv.2201.05132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperparameter Importance for Machine Learning Algorithms

Abstract: Hyperparameter plays an essential role in the fitting of supervised machine learning algorithms. However, it is computationally expensive to tune all the tunable hyperparameters simultaneously especially for large data sets. In this paper, we give a definition of hyperparameter importance that can be estimated by subsampling procedures. According to the importance, hyperparameters can then be tuned on the entire data set more efficiently. We show theoretically that the proposed importance on subsets of data is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The lack of variation in the direction of SHAP values for the ANN model contrasted sharply with the XGBoost model and suggested that the former may not be capturing the true underlying data patterns. This discrepancy emphasizes the need for a thorough cross-validation and hyperparameter tuning process, which has been identified as a crucial step in model development [ 113 , 114 ]. Furthermore, the negative R² score suggests that the ANN model’s predictive power was worse than a naïve model, which would simply predict the average a/b ratio for all observations [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of variation in the direction of SHAP values for the ANN model contrasted sharply with the XGBoost model and suggested that the former may not be capturing the true underlying data patterns. This discrepancy emphasizes the need for a thorough cross-validation and hyperparameter tuning process, which has been identified as a crucial step in model development [ 113 , 114 ]. Furthermore, the negative R² score suggests that the ANN model’s predictive power was worse than a naïve model, which would simply predict the average a/b ratio for all observations [ 115 ].…”
Section: Discussionmentioning
confidence: 99%